The relationship between intrinsic capacity and functional ability in older adults - Somayeh Ahmadi; Pouya Farokhnezhad Afshar; Kazem Malakouti; Mojtaba Azadbakht (BMC Geriatrics)
Abstract Introduction Intrinsic Capacity in integrated geriatric care emphasizes the importance of a thorough functional assessment. Monitoring the intrinsic capacity of older individuals provides standardized and reliable information to prevent early disability. This study assessed the relationship between intrinsic capacity and functional ability in older adults. Method This cross-sectional study involved 210 older individuals aged 60 and above referred to Rasoul Akram Hospital. Data collection included ADL and IADL scales, the Snellen chart, the Hearing Handicap Inventory, the hand dynamometer, the TUG test, the AMT test, and the GDS. Data analysis was conducted using SPSS software v.26 via independent t-tests, ANOVA, Pearson correlation coefficient, and multiple regression analysis. Results The participants were 70.13 ± 7.04 years. 57.6% were older females and 42.4% were older males. Age showed a significant and inverse correlation with both ADL (P < 0.001, r = -0.23) and IADL (P < 0.001, r = -0.39). The adjusted coefficient of determination (R²) for the five domains of intrinsic capacity (sensory, cognitive, locomotion, psychological, vitality) as well as age and BMI was 0.16 for ADL and 0.32 for IADL. Conclusion Age and TUG could only weakly explain ADL changes, while vision, hand grip strength, cognition, and age had moderate predictive ability of IADL. Therefore, by assessing these predictors, we can predict disability before it occurs and make necessary interventions.